2005
DOI: 10.1007/s00223-004-0147-4
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine and Isovaleryl L-Carnitine Fumarate Positively Affect Human Osteoblast Proliferation and Differentiation In Vitro

Abstract: Age-related bone loss is characterized by decreased osteoblast activity, possibly related to the reduction of energy production. Carnitine promotes energy availability and its concentration declines with age; Therefore, two Carnitine derivatives, L-carnitine fumarate (LC) and isovaleryl L-carnitine fumarate (Iso-V-LC), have been tested on several parameters of human osteoblasts in vitro. Both compounds significantly increased osteoblast activity, but the new compound Iso-V-LC was more efficient than LC at lowe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 22 publications
2
31
0
1
Order By: Relevance
“…Some studies suggest that LC promoted osteoblast proliferation and differentiation in vitro (43,44), while other studies indicated that LC inhibited proliferation in VSMCs (45). In this study, we found that the 10 μM LC positively affected osteoblast proliferation, but the higher concentration of LC (100 μM) slightly decreased osteoblast proliferation compared with the control.…”
Section: Discussionmentioning
confidence: 41%
See 1 more Smart Citation
“…Some studies suggest that LC promoted osteoblast proliferation and differentiation in vitro (43,44), while other studies indicated that LC inhibited proliferation in VSMCs (45). In this study, we found that the 10 μM LC positively affected osteoblast proliferation, but the higher concentration of LC (100 μM) slightly decreased osteoblast proliferation compared with the control.…”
Section: Discussionmentioning
confidence: 41%
“…Studies indicated that cells of the osteoblastic lineage generate 40% to 80% of their energy demands through fatty acid β-oxidation (14). It has also been demonstrated that LC could protect osteoblastic cells from apoptosis (15,16), increased metabolic activity and protein production of porcine osteoblast-like cells (17), as well as affected osteoblastic activity (15).…”
Section: Introductionmentioning
confidence: 99%
“…Formerly it was shown that these two compounds stimulate osteoblasts proliferation and differentiation by co-operation of insulinlike growth factors (IGFs) [129]. Also in osteoporotic pregnant mice Iso-V-LC and to a lesser extent LC accelerated bone recovery after a hypocalcemic diet [130].…”
Section: L-carnitinementioning
confidence: 99%
“…Using an aging ovariectomized rat model they found supplementation of L-carnitine can influence bone density and slow the rate of bone turnover by slowing bone loss and improving bone microstructural properties through decreasing bone turnover (Hooshmand et al 2008). Also, Colucci et al (2005) used an in vitro model to suggest that carnitine supplementation in the elderly may stimulate osteoblast activity and decrease age-related bone loss. The apoptotic changes seen in the OVX rats' myofibers were hardly detected in L-carnitine treated group.…”
Section: Discussionmentioning
confidence: 97%